First Report of Powdery Mildew Caused By Podosphaera xanthii on Ageratum conyzoides, in Indonesia - Siska Arie Santy Siahaan; Jamjan Meeboon; Iman Hidayat; Kartini Kramadibrata; Arvita Netti Sihaloho; Ika Rosenta Purba (International Journal of Science and Environment (IJSE), 2026)
Powdery mildew is one of the most common and important fungal diseases and maycause huge economic losses to crop yields worldwide. During survey of powderymildews in 2011 and 2013, six samples of Ageratum conyzoides were collected fromdifferent regions in Indonesia, i.e. Bali, South Sumatera and West Java provinces.Anamorphic features revealed that the fungus belongs to the genus Podosphaera. Twosets of sequences of both ITS rRNA and 28S regions were obtained from the sixsamples. Phylogenetic analyses, including maximum parsimony (MP) and maximumlikelihood (ML) were executed using MEGA7. The strength of internal branches ofthe resulting trees were tested with bootstrap analysis. Tree scores, including treelength, CI, RI and RC were also calculated. The phylogenetic analysis confirmed thatthe fungus belongs to the genus Podosphaera, forming a clade with the sequencesfrom Podosphaera xanthii. This is the first report of powdery mildews on Ageratumconyzoides from Indonesia.